The Study of Reservations and Concerns in Application of 360° Feedback System - Sharma, Deepak; Singhal, R. K (Journal of Commerce and Trade, 2017)
The main aim of the study is to analyze the effectiveness of 360-degree performance appraisal feedback system in Anand Publications and Nageen Publications. Performance evaluation techniques are often driven by a desire to minimize disagreement across evaluations. Historically, the typical goal of maximizing agreement is based on the assumption that there exists an objective reality that will be similarly perceived and reported, despite differences in rater perspective. The responses are presented collectively to the assessee in the form charts and graphs. Comments and interpretations are presented later. Counselling sessions are arranged with the employee to remove the weaknesses identified in the Three sixty degree assessment. A sample size of 100 employees is chosen. Out of which 50 employees were from Anand Publications and remaining 50 from Nageen Publication. Companies that implement 360° feedback without first developing good managers who can give feedback correctly risk serious damage to teamwork and morale. Providing constructive feedback calls for instruction, training and practice. Any organization considering using 360° feedback in the appraisal process should begin by using for development purpose only and then gradually to make it a part of appraisal system. JEL Classification : E 24, P 47.